2011
DOI: 10.2967/jnumed.111.089730
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Imaging with18F-Florbetaben in Alzheimer Disease and Other Dementias

Abstract: Amyloid imaging with 18 F-labeled radiotracers will allow widespread use, facilitating research, diagnosis, and therapeutic development for Alzheimer disease. The purpose of the study program was to compare cortical amyloid deposition using 18 F-florbetaben and PET in controls and subjects with mild cognitive impairment (MCI), frontotemporal lobar degeneration (FTLD), dementia with Lewy bodies (DLB), vascular dementia (VaD), Parkinson disease (PD), and Alzheimer disease (AD). Methods: One hundred nine subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
272
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(295 citation statements)
references
References 44 publications
13
272
1
3
Order By: Relevance
“…This study also demonstrated the ability of diagnosing AD from other neurodegenerative disorders (p < 0.001), including vascular dementia, DLB, and frontotemporal lobar dementia [38]. A phase 0 trial demonstrated the safety and efficacy of this drug.…”
Section: [ 18 F]-av-1 or [F-18]-bay94-9172 Or Florbetabenmentioning
confidence: 67%
“…This study also demonstrated the ability of diagnosing AD from other neurodegenerative disorders (p < 0.001), including vascular dementia, DLB, and frontotemporal lobar dementia [38]. A phase 0 trial demonstrated the safety and efficacy of this drug.…”
Section: [ 18 F]-av-1 or [F-18]-bay94-9172 Or Florbetabenmentioning
confidence: 67%
“…Amyloid burden in PDD patients is heterogeneous with cases of PDD, where amyloid deposition overlaps with the levels observed in healthy subjects and in PD patients (Edison et al, 2013(Edison et al, , 2008Foster et al, 2010;Gomperts et al, 2012Gomperts et al, , 2008Jokinen et al, 2010;Maetzler et al, 2009Maetzler et al, , 2008 and other cases of PDD showing elevated cortical amyloid deposition in the Alzheimer's disease (AD) range (Edison et al, 2013(Edison et al, , 2008Foster et al, 2010;Gomperts et al, 2012;Jokinen et al, 2010;Maetzler et al, 2009Maetzler et al, , 2008Shimada et al, 2013). In contrast, amyloid burden is usually elevated in DLB patients compared to healthy subjects and PD patients and the incidence ranges between 33% and 100% (Burke et al, 2011;Claassen, Lowe, Peller, Petersen, & Josephs, 2011;Edison et al, 2008;Foster et al, 2010;Gomperts et al, 2012Gomperts et al, , 2008Graff-Radford et al, 2012;Kantarci et al, 2012;Maetzler et al, 2009Maetzler et al, , 2008Rowe et al, 2007;Siderowf et al, 2014;Villemagne et al, 2011).…”
Section: Misfolded Proteinsmentioning
confidence: 99%
“…However, extracellular Aβ-amyloid plaques and intracellular tau neurofibrillary tangle are also observed at autopsy in PD, PDD, and DLB patients (Horvath, Herrmann, Burkhard, Bouras, & K€ ovari, 2013;Jellinger & Attems, 2008;Jellinger, Seppi, Wenning, & Poewe, 2002 of amyloid deposition in PD, PDD, and DLB. Overall these studies found that amyloid deposition tends to be modest in PD with normal cognition occurring in about 0%-13% of PD patients (Edison et al, 2013(Edison et al, , 2008Foster et al, 2010;Gomperts et al, 2012Gomperts et al, , 2008Johansson et al, 2008;Jokinen et al, 2010;Maetzler et al, 2009;Siderowf et al, 2014;Villemagne et al, 2011). Amyloid burden is generally low in PD subjects with mild cognitive impairment (MCI), and does not distinguish cognitively normal PD patients from PD-MCI (Foster et al, 2010;Gomperts et al, 2012Gomperts et al, , 2013Petrou et al, 2012).…”
Section: Misfolded Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the advent of three new radiotracers, which are currently at various stages of FDA assessment and approval, has brought amyloid imaging to the doorstep of clinical use. Recent clinical studies on florbetapir (AV-45), florbetaben (BAY-94), and flutemetamol (GE-067) claim to have demonstrated an ability to discriminate between AD patients and healthy controls with high degrees of sensitivity and specificity [6][7][8][9][10][11]. However, the theoretical bases of and ubiquitous patterns in the reported data raise a host of lingering questions that should be addressed before these radiotracers are clinically approved.…”
Section: Introductionmentioning
confidence: 99%